2016
DOI: 10.4236/acs.2016.62029
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Ice: Decadal Simulations and Future Scenarios Using BESM-OA

Abstract: Important international reports and a significant number of scientific publications have reported on the abrupt decline of Arctic sea ice and its impact on the Global Climate System. In this paper, we evaluated the ability of the newly implemented Brazilian Earth System Model (BESM-OA) to represent Arctic sea ice and sensitivity to CO 2 forcing, using decadal simulations (1980-2012) and future scenarios (2006-2100). We validated our results with satellite observations and compared them to Coupled Model Interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…(shortwave plus longwave) radiation closure at TOA, it shows deficiency in representing shortwave radiation over the Arctic and the ocean near the Antarctic (Casagrande et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(shortwave plus longwave) radiation closure at TOA, it shows deficiency in representing shortwave radiation over the Arctic and the ocean near the Antarctic (Casagrande et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More than that, BESM has the objective of being an additional climate model with ability of reproduce changes that are physically understood in order to study the global climate system. In this sense, a new version of BESM is under development in order to overcome the present extra-tropical and tropical climate simulation deficiencies, as reported in Casagrande et al (2016) and Veiga et al (2018), respectively. Notwithstanding, the inter-model spread in climate sensitivity discussed here, mainly that regarding the cloud feedback, remains a scientific challenge for the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result was found for the sea ice simulation from BESM model (See in Figure 2). Additionally, Casagrande et al,(2016), using BESM-OA V2.3 model, showed that the sea 200 ice spatial pattern could vary largely between CMIP5 models, especially in frontiers areas.…”
Section: Polar Amplificationmentioning
confidence: 99%
“…An ice model, called Sea Ice Simulator (SIS), is included in MOM5. SIS acts as an interface between the atmospheric and oceanic models, being responsible for calculating the fluxes ocean/ice and ice/atmosphere, and for communicating ocean/atmosphere fluxes on regions where there is no real ice [Casagrande et al 2016].…”
Section: Besm Climate Modelmentioning
confidence: 99%